Die gebruik van kleur in aanlyn woordeboeke, met oorweging van drie Afrikaanse woordeboeke - Adshade, Maryna (Lexikos, 2025)
The Use of Colour in Online Dictionaries, with Consideration of Three Afrikaans Dictionaries. When considering the use of colour in some online Afrikaans dictionaries, it seems that colour is sometimes used ineffectively or haphazardly. In other cases, colours seem to be chosen mainly to align with the dictionary publisher’s brand identity, rather than for practical purposes. This may result from abstract or vague metalexicographical suggestions that offer unsatisfactory guidance to practical lexicographers but could also be the result of South African, and Afrikaans, lexicography developing slower compared to the Western world. This article discusses the use of colour is in online dictionaries, considering a few suggestions from metalexicographical research. These suggestions are then supplemented with some guidelines derived from the field of information technology. The application of the theoretical possibilities, or lack thereof, is discussed with regard to the online version of the Handwoordeboek van die Afrikaans Taal, Aanlyn Woordeboek van die Afrikaans Taal and the Woordeboek van Afrikaans Vandag. These dictionaries show room for improvement in some aspects related to colour usage, with many exciting and more advanced possibilities still a future prospect for Afrikaans lexicography. Nevertheless, it is noteworthy that the use of colour is promising and may play a greater role in accessibility in the future. Keywords: colour usage, online dictionaries, data accessibility, dictionary structures, article structure